An exploratory study on the USARP method: improving the usability requirements elicitation and specification - Marques, Anna Beatriz; Fiori, Maria Victoria; Ferreira, Bruna (Cadernos do IME - Série Informática, 2024)
USARP (USAbility Requirements with Personas and User stories) is a method for eliciting and specifying usability requirements using personas, user stories, and usability guidelines organized as cards. USARP suggests brainstorming sessions to discuss usability requirements oriented by its cards. We conducted an exploratory study in an academic environment to analyze the use of USARP in projects developed by undergraduate students acting as software engineers. We noted difficulties in selecting cards to use during the USARP adoption. Thus, this study proposes to evolve USARP to provide a more effective way to elicit and specify usability requirements. We reviewed the cards, removing redundant content and combining cards with similar content. Also, we proposed a checklist and a board to guide the selection of the cards according to users and system characteristics. Finally, the process suggested for adopting USARP was updated to reflect the use of the new artifacts. In this extended version, we provide an example of USARP in practice. We expect these improvements could guide the customization of the brainstorming sessions to be more effective and efficient.